Compression of Morbidity 1980–2011: A Focused Review of Paradigms and Progress - James F. Fries; Bonnie Bruce; Eliza Chakravarty (Journal of Aging Research)
The Compression of Morbidity hypothesis—positing that the age of onset of chronic illness may be postponed more than the age at death and squeezing most of the morbidity in life into a shorter period with less lifetime disability—was introduced by our group in 1980. This paper is focused upon the evolution of the concept, the controversies and responses, the supportive multidisciplinary science, and the evolving lines of evidence that establish proof of concept. We summarize data from 20-year prospective longitudinal studies of lifestyle progression of disability, national population studies of trends in disability, and randomized controlled trials of risk factor reduction with life-style-based “healthy aging” interventions. From the perspective of this influential and broadly cited paradigm, we review its current history, the development of a theoretical structure for healthy aging, and the challenges to develop coherent health policies directed at reduction in morbidity.